1996
DOI: 10.1002/jor.1100140621
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of structural elastic fiber and collagen genes in familial adolescent idiopathic scoliosis

Abstract: Adolescent idiopathic scoliosis is a genetic disorder of unknown etiology. Scoliosis is a clinical feature of inherited connective-tissue disorders including Marfan syndrome. Mutations within the gene of FBN1 (fibrillin 15), a component of the extracellular matrix, are now linked to Marfan syndrome and similar clinical phenotypes. This study investigated the potential association of structural genes encoding for extracellular matrix components of FBN1, elastin, and one of the polypeptides of type-I collagen (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 37 publications
0
33
0
5
Order By: Relevance
“…[9][10][11][12][13][14][15][16] Several candidate gene studies have also reported that genes such as COL1A1, COL1A2, FBN1, ESR, MATN1, MTNR1B, CHD7, VDR and GPER were associated with scoliosis. 10,[17][18][19][20][21][22][23][24] Recently, a genome-wide association study (GWAS) has been applied to identify the susceptibility loci of AIS. 25 The single nucleotide polymorphism (SNP) rs11190870 that is located in the 3¢-flanking region of LBX1 (ladybird homeobox 1) gene at chromosome 10q24.31 was identified as the most significant common variant in Japanese females with P¼1.24Â10 19 ; odds ratio (OR)¼1.56.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Several candidate gene studies have also reported that genes such as COL1A1, COL1A2, FBN1, ESR, MATN1, MTNR1B, CHD7, VDR and GPER were associated with scoliosis. 10,[17][18][19][20][21][22][23][24] Recently, a genome-wide association study (GWAS) has been applied to identify the susceptibility loci of AIS. 25 The single nucleotide polymorphism (SNP) rs11190870 that is located in the 3¢-flanking region of LBX1 (ladybird homeobox 1) gene at chromosome 10q24.31 was identified as the most significant common variant in Japanese females with P¼1.24Â10 19 ; odds ratio (OR)¼1.56.…”
Section: Introductionmentioning
confidence: 99%
“…Several forms of inheritance of idiopathic scoliosis have been proposed including multifactorial [Berven et al, 1997;Wynne-Davies, 1968], X-linked [Cowell et al, 1972] and autosomal dominant [Aksenovich et al, 1988;Bell and Teebi, 1995;Bonaïti-Pellié et al, 1976;Carr et al, 1992;Garland, 1934;Miller et al, 1996;Robin and Cohen, 1975]. Genetic heterogeneity has been suggested by Bonaïti-Pellié et al [1976], who showed that the distribution of the disorder in families of 241 patients could be interpreted in terms of a major autosomal gene with incomplete penetrance and more frequent manifestation in girls than boys, or else in terms of genetic heterogeneity with a mixture of dominant and multifactorial models of inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…Ces différents changements de points de vue sont résumés au Tableau 1. En définitive, l'analyse des gènes codant pour ces différentes composantes a permis d'exclure la moindre implication de ces gènes dans l'étiopa-thogénie de la scoliose [13,14]. Conséquemment, les modifications observées dans la SIA seraient plutôt des événements secondaires associés à cette maladie : et ils se limiteraient seulement à l'aggravation des défor-mations.…”
Section: éLéments Structuraux Du Rachisunclassified